Smart Fishpond System Design for Pearl Catfish Cultivation Based on LoRa WAN - Rachmaningrum, Nilla; Duta, Muhammad Arya Duta; Untsa, Risdilah Mimma Untsa (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
The application of industrial revolution 4.0 technology in the fisheries sector in Indonesia has a percentage of 8% so it needs to be developed by designing an integrated system. In the fisheries sector, water quality plays an important role as a medium for fish breeding. Integrated system design can be done to maintain the quality and temperature of pond water. Pearl Catfish farming requires special attention to water pH, temperature, and appropriate feeding. Manual checking of water conditions is less accurate and inefficient. An automation system with temperature and pH meter sensors integrated via LoRa WAN enables automatic monitoring and feeding. This research aims to produce a tool that controls water conditions and feeds automatically. The ideal water temperature for Pearl Catfish is 15-30℃ with pH 5-10 and ammonia < 3mg/L. Temperature control is done by watering the pond or using a peltier as a cooler. pH outside the range will activate automatic draining and filling. Tests were conducted in a pond with Pearl Catfish, with successful tests if the pH and temperature were appropriate. The device has a delay and can be accessed without internet via LoRa WAN.